Automating Repetitive Tasks for the Masses - Gulwani, Sumit (POPL '15 Proceedings of the 42nd Annual ACM SIGPLAN-SIGACT Symposium on Principles of Programming Languages, 2015)
The programming languages (PL) research community has traditionally catered to the needs of professional programmers in the continuously evolving technical industry. However, there is a new opportunity that knocks our doors. The recent IT revolution has resulted in the masses having access to personal computing devices. More than 99% of these computer users are non-programmers and are today limited to being passive consumers of the software that is made available to them. Can we empower these users to more effectively leverage computers for their daily tasks? The formalisms, techniques, and tools developed in the PL and the formal methods research communities can play a pivotal role!